Cutting Sugar Cane, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A labourer cutting the cane stalks in the field.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry--Trinidad and Tobago; Sugarcane--Trinidad and Tobago; Working class--Trinidad and Tobago